Biosynthesis of thromboxane in patients with systemic sclerosis and Raynaud's phenomenon. - Reilly, I A (1986)
Thromboxane A2, the predominant cyclo-oxygenase product of arachidonic acid in platelets, is a potent vasoconstrictor and platelet agonist. Analysis of urinary metabolites by gas chromatography and mass spectrometry is a specific non-invasive method of measuring the biosynthesis of thromboxane that avoids the problem of platelet activation ex vivo. Excretion of the major urinary thromboxane metabolite, 2,3-dinor-thromboxane B2, was significantly increased (p less than 0.001) in 10 patients (nine women) with systemic sclerosis complicated by Raynaud's phenomenon compared with healthy controls (486 (SD 88) v 162 (38) ng/g creatinine) and increased further in the patients (to 1007 (212) ng/g creatinine) during application of a cold stimulus sufficient to induce digital vasoconstriction. Consistent with an increase in platelet-vascular interactions in vivo, excretion of a prostacyclin metabolite was also significantly increased (p less than 0.005) in the patients with systemic sclerosis (248 (39) v 112 (10) ng/g creatinine) and tended to increase further on cooling. Biosynthesis of thromboxane is increased in patients with systemic sclerosis and may exacerbate digital vasospasm that such patients develop when cold. This observation and the concomitant increase in the formation of prostacyclin provide a rationale for evaluating compounds that prevent the synthesis of thromboxane A2 or inhibit its action while preserving the potential homoeostatic role of prostacyclin.